2011
DOI: 10.1086/662128
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Analysis of Allocation to Sexual and Clonal Reproduction inPenthorum sedoidesunder Contrasting Nutrient Levels

Abstract: Reproductive output and reproductive allocation are important factors in the life history of any organism. In clonal plants, however, ''reproductive'' can refer to both sexual and asexual (clonal) replication. When investigating reproductive allocation, it is essential that the size of the plants studied be taken into account and that the direct analysis of ratios (e.g., fruit mass/vegetative mass) be avoided. Using methods that allow the testing of both a minimum size of reproduction and nonlinearity in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
10
1
1
Order By: Relevance
“…Experiments on herbaceous plants demonstrate that varying environmental factorsnamely resource availability and competitioninduce plasticity in reproductive strategies (Sultan, 2000;Weiner et al, 2009b;Anderson et al, 2011;Nicholls, 2011). In addition, plant populations are often genetically differentiated along environmental clines for size at reproduction and reproductive allometry, that is, the relationship between reproductive output and vegetative size (Lacey, 1988;Alexander et al, 2009;Guo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on herbaceous plants demonstrate that varying environmental factorsnamely resource availability and competitioninduce plasticity in reproductive strategies (Sultan, 2000;Weiner et al, 2009b;Anderson et al, 2011;Nicholls, 2011). In addition, plant populations are often genetically differentiated along environmental clines for size at reproduction and reproductive allometry, that is, the relationship between reproductive output and vegetative size (Lacey, 1988;Alexander et al, 2009;Guo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…buds on the layering that are the primary shoot-producing meristematic organs [34], [35], [36], [37], [38]. The clonal growth of a size-dependent clone is common [33], [38], [39], [40], [41]. One study found that the big Glechoma hederacea clone developed a greater number of ramets under favorable conditions [38].…”
Section: Introductionmentioning
confidence: 99%
“…In nutrient-poor soils, plants may allocate more resources for sexual structures in L. chinensis (Bai et al 2009), P. sedoides (Nicholls 2011), and Trapella sinensis (Liu et al 2013) (see Table 1) because sexual reproduction has the potential to produce genetic variations, which could increase the survivorship of the plants in the future (Grant 1981;Philbrick and Les 1996). Moreover, seeds may serve as a potential escape mechanism for offspring (Choo et al 2015;Nicholls 2011;van Kleunen et al 2002). The increase in the sexual biomass indicates that the plant might favor from founding new populations instead of expanding the current population through seed dispersal and seed bank under conditions of scarcity of resources.…”
Section: A General Trend On Selection Of Reproductive Modes In Relatimentioning
confidence: 99%